Servant Leadership and Work-Life Balance as Predictors of Organizational Commitment among Public High School Teachers - Putri Inayah; Rosita Endang Kusmaryani (Universitas Muhammadiyah Mataram, 2026)
Organizational commitment is essential for maintaining teachers’ loyalty in public schools. This study examines the roles of servant leadership and work–life balance in predicting organizational commitment among public senior high school teachers in Sarolangun Regency, Jambi. Using a quantitative survey design, data were collected from 190 teachers through multistage random sampling and analyzed using multiple linear regression. The results show that servant leadership and work–life balance jointly influence organizational commitment. However, partial analysis indicates that servant leadership has no significant effect, whereas work–life balance has a significant positive effect on organizational commitment. These findings highlight work–life balance as a key factor in strengthening teachers’ organizational commitment, suggesting the importance of supportive work policies in public school settings.Organizational commitment is essential for maintaining teachers’ loyalty in public schools. This study examines the roles of servant leadership and work–life balance in predicting organizational commitment among public senior high school teachers in Sarolangun Regency, Jambi. Using a quantitative survey design, data were collected from 190 teachers through multistage random sampling and analyzed using multiple linear regression. The results show that servant leadership and work–life balance jointly influence organizational commitment. However, partial analysis indicates that servant leadership has no significant effect, whereas work–life balance has a significant positive effect on organizational commitment. These findings highlight work–life balance as a key factor in strengthening teachers’ organizational commitment, suggesting the importance of supportive work policies in public school settings.